Cross-Generational Contributors to Preterm Birth in California: Singletons Based on Race/Ethnicity - Francois, Lissa N.; Yang, Juan; Baer, Rebecca J.; Chung, Paul J.; Jelliffe-Pawlowski, Laura L.; Coker, Tumaini R. (American Journal of Perinatology, 2019)
Objective Multiple studies have examined cross-generational patterns of preterm birth (PTB), yet results have been inconsistent and generally focused on primarily white populations. We examine the cross-generational PTB risk across racial/ethnic groups.Study Design Retrospective study of 388,474 grandmother–mother–infant triads with infants drawn from birth registry of singleton live births between 2005 and 2011 in California. Using logistic regression (odds ratios [ORs] and confidence intervals [CIs]), we examined the risk of preterm delivery by gestational age, sociodemographic, socioeconomic, and obstetric clinical characteristics stratified by maternal race/ethnicity.Results The risk of having a preterm infant <32 weeks was greater for women born at <32 weeks (OR: 2.09, 95% CI: 1.62–2.70) and 32 to 36 weeks (OR: 1.51, 95% CI: 1.35–1.70). This increased risk of preterm delivery was present among women in all race/ethnicity groups (white [AOR: 2.00, 95% CI: 1.52–2.63), black [AOR: 1.79, 95% CI: 1.37–2.34], Hispanic [AOR: 2.39, 95% CI: 2.05–2.79], and Asian [AOR: 2.12, 95% CI: 1.20–3.91]), with hypertension as the only consistent risk factor associated with increased risk of preterm delivery.Conclusion Our findings suggest a cross-generational risk of PTB that is consistent across race/ethnicity with hypertension as the only consistent risk factor.
Keywords: birth; outcome; gestational age; preterm birth